Glycated Haemoglobin (HbA1c) peak in Capillary Zone Electrophoresis (CZE) among Diabetes Mellitus (DM) individuals - Baharom, Fatin Akmal; Mohd. Tohit, Eusni Rahayu; Md Noor, Sabariah; Osman, Raudhawati (Universiti Putra Malaysia, 2021)
Introduction: Capillary zone electrophoresis (CZE) is a method of haemoglobin (Hb) analysis for the screening of haemoglobinopathies or variant haemoglobins. In our centre, few samples sent for Hb analysis showed Hb peak at zone 10 requiring further evaluation. This pattern was observed in patients with history of diabetes mellitus (DM); hence it was postulated the peak observed is glycated Hb (HbA1c). The objective of this study was to determine whether the expression of Hb peak at zone 10 among blood samples from DM patients correlate with HbA1c values measured using high performance liquid chromatography (HPLC). Methods: This was a cross-sectional study involving blood samples from DM patients. Samples with HbA1c values ≥ 6.5% by HPLC were selected and subsequently analysed by CZE method. Presence of Hb peak in zone 10 were correlated and analysed with the HbA1c levels measured by HPLC method. Results: A total of 131 samples were analysed. Hb peak was detected at zone 10 in 50/131(38.2%). Out of 50 samples, 47 (94%) were from patients with HbA1c level > 10%. Correlation study showed it was 18 times more likely for Hb peak to appear in zone 10 in patients with HbA1c > 10%. Cut off point for HbA1c to appear in CZE is 10.5% with AUC of 0.965. Conclusion: Hb peak detected at zone 10 of CZE was most likely to be HbA1c. However, it is recommended that for every primary method of Hb analysis used be confirmed by secondary method. Therefore, both zone 10 in CZE and P2 peak in HPLC must be correlated together to achieve final diagnosis.